Editorial. Architectural competitions I - Exploring the phenomenon of competing in architecture and urban design - Andersson, Jonas E; Rönn, Magnus; Östman, Leif (FormAkademisk, 2013)
The combination of realising buildings with such architectural care that they become high-quality architecture and the momentum of introducing a competitive phase in this creative work may strike most people as odd. However, the phenomenon dates back to the Olympic Games of Ancient Greece, where the harmony between aesthetics and architectural realisation was assessed in a public voting process.